Abbie Rosner: Breaking Bread in Galilee – A Culinary Journey into the Promised Land - Jaine, Tom (Petits Propos Culinaires, 2012)
Abbie Rosner: Breaking Bread in Galilee – A Culinary Journey into the Promised Land: Hilayon Press, Israel, 2012, 238 pp., paperback, $15.00.